Analysis of nursing workforce policy impacts on healthcare quality and equity using a prospective cohort study design - Suprapto Suprapto (Lembaga Edukasi Ilmiah Indonesia, 2026)
Introduction: Nursing workforce policies are critical determinants of healthcare system performance, particularly in improving care quality and reducing inequities. However, longitudinal evidence assessing their causal impact remains limited. This study aimed to analyze the effects of nursing workforce policy implementation on healthcare quality and equity outcomes using a prospective cohort design. Methods: A prospective cohort study was conducted across public and private healthcare facilities in South Sulawesi, Indonesia (2025). A multistage stratified sampling approach yielded 862 participants. Policy exposure was categorized into low, moderate, and high levels based on staffing regulations, skill mix, and workload management. Data were collected at baseline and follow-up intervals using validated instruments and administrative records. Multilevel regression models were applied, including logistic regression for patient safety events, linear regression for continuous outcomes, and risk ratio estimation for equity indicators. Results were reported as OR/β/RR with 95% confidence intervals (CI) and p-values. Results: High policy exposure significantly reduced patient safety events (OR = 0.62; 95% CI: 0.45–0.85; p = 0.003). Length of stay decreased (β = −1.75; 95% CI: −2.80 to −0.70; p = 0.001), while patient satisfaction increased (β = 3.42; 95% CI: 1.90–4.94; p < 0.001). Equity outcomes improved significantly (RR = 1.28; 95% CI: 1.10–1.49; p = 0.002). These findings remained robust after adjusting for individual and facility-level confounders. Conclusion: Nursing workforce policy implementation significantly enhances healthcare quality and promotes equity. Strengthening staffing regulations, optimizing skill mix, and ensuring consistent policy enforcement are essential strategies to improve health system performance. Integrating workforce policies with governance and financing mechanisms is crucial for achieving sustainable and equitable healthcare outcomes.